PENERAPAN METODE DEMONSTRASI MELALUI PEMBELAJARAN SAINS PADA ANAK KELOMPOK A DI RA ASSA’IDIYYAH KARANGLPOSO - Sutriani Sutriani; Mohammad Afifulloh; Ika Anggraheni (Jurnal Dewantara, 2021)
This study is about describing the application of the demonstration method in science learning at RA Assa'idiyyah, Karangploso district, Malang Regency. The form of this research is descriptive qualitative research. Qualitative methods are used to examine the condition of an object naturally, in this study the subjects used were early childhood in RA Assa'idiyyah aged 4-5 years, based on the results of research and data collection techniques were carried out by triangulation (interviews, observations, documentation). ) it is known that: 1) Learning planning has been carried out by the teacher, including: preparing RPPM (Weekly Learning Implementation Plan), preparing RPPH (Daily Learning Implementation Plan), determining themes and objectives, preparing learning media or materials, 2) Implementing lessons that have been carried out in accordance with RPPH with preliminary activities, core activities and closing; 3) Evaluation is carried out by giving assignments to work on BKS (student activity books) and conducting assessments. Some of the steps taken in the application of the demonstration method include: lesson planning, implementation of learning and evaluation of science learning through demonstration methods.